Penicillin-Susceptible Streptococcus pneumoniae Meningitis in Adults: Does the Ceftriaxone Dosing Matter? - Samuel Raemy; Carlo Casanova; Rossella Baldan; Erin Barreto; Aaron J. Tande; Andrea Endimiani; Stephen L. Leib; Urs Fischer; Parham Sendi (MDPI AG, 2023)
The recommended empiric ceftriaxone dosing regimen for acute bacterial meningitis in adults is 2 g every 12 h. After penicillin-susceptible Streptococcus pneumoniae is isolated as a causative microorganism, the ceftriaxone dose may be continued or reduced to a single dose of 2 g every 24 h, per institutional preference. There is no clear guidance that indicates the superiority of one regimen over the other. The objective of this study was to evaluate the susceptibility of S. pneumoniae in the cerebral spinal fluid (CSF) of patients with meningitis and the relationship between ceftriaxone dose and clinical outcomes. We identified 52 patients with S. pneumoniae meningitis with positive CSF cultures who were treated at the University Hospital, Bern, Switzerland, over a 19-year period. We collected clinical and microbiological data for evaluation. Broth microdilution and Etest methods were performed to test penicillin and ceftriaxone susceptibility. All isolates were susceptible to ceftriaxone. Ceftriaxone was empirically used in 50 patients, with a starting dosing regimen of 2 g every 24 h in 15 patients and 2 g every 12 h in 35 patients. In 32 patients started on a twice-daily regimen (91%), doses were reduced to once daily after a median of 1.5 (95% CI 1-2) days. The overall in-hospital mortality was 15.4% (n = 8), and 45.7% of patients reported at least one sequela of meningitis at the last follow-up (median 375, 95% CI 189-1585 days). We found no statistical difference in outcome between the 2 g every 24 h and the 2 g every 12 h ceftriaxone dosing regimens. A ceftriaxone total daily dose of 2 g may be associated with similar outcomes to a 4 g total daily dose, provided that the causative organism is highly susceptible to ceftriaxone. The persistence of neurological and infection sequelae at the last follow-up underscores the need for optimal treatment of these complex infections.